Legislating for fair competition : a comparison of some provisions of the Jamaican and United States legislation. - PAULWELL, Phillip (1994)
Notes that the laws of both the US and Jamaica seek to combine dual objectives in competition policy and consumer protection. Firstly, effective competition leads to greater efficiency and greater productivity and will ultimately benefit the consumers by way of lower prices, more choices and product innovation. Secondly, consumer protection ensures fair competition by preventing those who would deceive consumers from diverting trade from those who compete honestly.